External forces in alpine sit-skiing vs. athletes' strength abilities: Consequences for development of evidence-based classification - Goll, M.; Spitzenpfeil, P.; Olvermann, M.; Huber, A. (Science and Skiing VII, 2018)
In all sports sanctioned by the International Paralympic Committee (IPC), a classification system regulates the athletes` eligibility to compete. For this, the activity-limiting factors direct the allocation of athletes to their respective competition class by clustering athletes in groups of similar abilities or levels of activity impairment. The latest version of the IPC`s classification code was approved in 2007 and established the guidelines and procedures, and mandates the development of an evidence-based classification system oriented at sport-specific characteristics of the individual discipline (International Paralympic Committee, 2007). The IPC Alpine Skiing Classification Rules and Regulations (International Paralympic Committee, 2015c) state that "the purpose of classification is to minimize the impact of eligible impairment types on the outcome of competition, so that athletes who succeed in competition are those with the best anthropometry, physiology, and psychology, and have enhanced them to the best effect," indicating that evidence-based classification is supposed to replace the current system in future. To do that, research in Paralympic alpine skiing is required concerning the eligibility criteria and the extent of activity limitations they cause and the relative strength of association between them (Tweedy & Vanlandewijck, 2011). This investigation focuses on the sitting class which is made up of athletes who compete in a sit-ski in five so-called locomotor winter (LW) classes: LW 12-2, LW 2 1, LW 11, LW 10-2, and LW 10-1, representing the increasing extent of activity limitation to the abdominal and back muscles.